A bistable memristor-based circuit system and its implementation. (24th December 2021) - Chen, Zhen; Li, Chunlai; Qian, Kun
This paper introduces a fourth-order oscillation circuit by replacing Chua's diode with a voltage-controlled memristor and removing the resistor of canonical Chua's circuit. The system equations are built based on the circuit theory, the dissipation of the system and the stability of the equilibrium point are analysed. Dynamic behaviours of the system have been studied by using phase portraits, bifurcation diagrams and Lyapunov spectrums. The analysis results show that the proposed system has bistability phenomenon of chaotic or periodic states and possesses complex transient dynamics under different parameter and initial conditions. This kind of bistability pattern reflects the sensitivity of system dynamics to initial condition, thus it can be used to generate random number and encrypt data information, and can also be used to realise bistable switch in the field of storage and computing. An analogue electronic circuit is then designed to verify the numerical simulation results.